2021
DOI: 10.1016/j.ijthermalsci.2020.106607
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evaluation of additively manufactured lattice architectures for heat sink applications

Abstract: Tailoring the architectural characteristics of lattice materials at different length scales, from nano to macro, has become tenable with emerging advances in additive manufacturing. Cumulative needs of high heat dissipation rates and structural requirements along with lightweight constraints have led to the development of several heat sink fins with lattice architectures in heat exchange-applications. Here, we numerically investigate the potential of polymer-based 3D printed lattice architectures as extended h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 51 publications
(69 reference statements)
0
11
0
Order By: Relevance
“…The criteria for damage initiation in the 3Dprinted ABS are based on Hashin's theory [54], which was originally developed for fibre-reinforced composite materials but can also be used for analysis of orthotropic materials [55] by using the definitions of the directions as described in Eqs. (5)(6)(7)(8).…”
Section: Essential Work Of Fracture Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The criteria for damage initiation in the 3Dprinted ABS are based on Hashin's theory [54], which was originally developed for fibre-reinforced composite materials but can also be used for analysis of orthotropic materials [55] by using the definitions of the directions as described in Eqs. (5)(6)(7)(8).…”
Section: Essential Work Of Fracture Assessmentmentioning
confidence: 99%
“…Additive manufacturing (AM), commonly known as 3D printing, has attracted the interest of the academic and industrial research community because of its ability to fabricate objects with complex geometries at relatively low cost and with high flexibility [1][2][3][4][5][6][7][8][9]. It is an emerging technology where structures are printed layer by layer with the help of computer-aided design (CAD) models.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that Kagome structures have desirable heat-dissipation properties due to the large hexagonal holes through which fluid may flow, compared to triangular and hexagonal cells. More recently, Dixit et al [ 63 ] concluded that octet topology dissipates more heat at the lowest Reynolds numbers while SC-BCC-truss outperforms other architectures as the fluid velocity increases.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in additive manufacturing, a part is built by layer-by-layer material addition, minimizing the overall waste of raw material [2]. Selective laser sintering, selective laser melting (very similar to selective laser sintering and differing primarily in the materials they use), electron beam melting, and direct metal laser sintering are the additive manufacturing methods dealing with metals [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…One feature of 3D-printed heat exchanging devices that is important to thermal performance is the minimization of contact thermal resistance caused by conventional attachment of elements on surfaces [4]. Aside from the plus points, the challenges of the additive manufacturing must be considered; overhang printing, removal of supporting structures, compatible raw materials, and minimization of the overall costs can be named as a few [2].…”
Section: Introductionmentioning
confidence: 99%